NITROGEN TRANSFORMATION IN FLOODED SOIL : APPLICATION OF RICE STRAW AND RICE STRAW COMPOSTS AND ITS EFFECT ON NITROGEN UPTAKE AND ACETYLENE REDUCTION ACTIVITY IN RICE PLANT RHIZOSPHERE - INDRIYATI, L.T; SABIHAM, SUPIYANDI; DARUSMAN, L.K; SITUMORANG, R.; SUDARSONO, .; SISWORO, W.H (Balai Besar Penelitian dan Pengembangan Sumberdaya Lahan Pertanian, 2007)
The use of organic materials aimed in reducing the dependence on inputs such as chemical fertilizers can contribute to sustainability and improving the low N fertilizer efficiency of rice plants in paddy soils. Therefore, better understanding of N transformation in flooded soils, particularly the microbial transformation of N-organic amendments to plant-available N, is needed for most efficient use of soil and organic materials N for aiding in the selection of N management practices for sustainable agriculture. The experiments were conducted at the laboratory and in the greenhouse of Soil Department, Faculty of Agriculture, Bogor Agricultural University. Incubation experiment was conducted at room temperature for 120 days to observe the availability of N-NH4+ in soil amended rice straw or rice straw composts and its combination with urea. After 21 days of incubation period, the rice straw amended soils showed that NNH4+ release was higher than the other treatments. The 4-monthand 8-month-compost of rice straw showed that N mineralization rate was lower and the N availability was lower than rice straw. The results of pot experiment in greenhouse revealed that the added rice straw was comparable with urea in its effect on the increase of dry matter weight of rice plants, number of tillers, Nuptake of rice, and recovery N efficiency. The application of rice straw, however, promoted the activity of nitrogenase enzyme higher than rice straw composts. The effect of rice straw on observed parameters were much better than its composts.